2010
DOI: 10.1093/nar/gkq568
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of thermal stability can enhance the potency of siRNA

Abstract: During RNA-induced silencing complex (RISC) assembly the guide (or antisense) strand has to separate from its complementary passenger (or sense) strand to generate the active RISC complex. Although this process was found to be facilitated through sense strand cleavage, there is evidence for an alternate mechanism, in which the strands are dissociated without prior cleavage. Here we show that the potency of siRNA can be improved by modulating the internal thermodynamic stability profile with chemical modificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 25 publications
3
54
1
Order By: Relevance
“…A variety of chemical modifications are compatible with siRNA activity, including 29-fluoro, 29-OMe, 2,4-difluorotoluene, phosphorothioate, and others . Such modifications have the potential to reduce immunostimulation, enhance serum stability, increase specificity, and improve activity Addepalli et al 2010). Manipulation of the naturally occurring 21-mer design has revealed that not only longer duplexes, such as dsiRNA, but also shorter duplexes and duplexes with altered overhangs participate in RNAi (Chu and Rana 2008;Chang et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…A variety of chemical modifications are compatible with siRNA activity, including 29-fluoro, 29-OMe, 2,4-difluorotoluene, phosphorothioate, and others . Such modifications have the potential to reduce immunostimulation, enhance serum stability, increase specificity, and improve activity Addepalli et al 2010). Manipulation of the naturally occurring 21-mer design has revealed that not only longer duplexes, such as dsiRNA, but also shorter duplexes and duplexes with altered overhangs participate in RNAi (Chu and Rana 2008;Chang et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This was recently applied to increase the immuno stimulatory properties of an siRNA targeting H5N1 in fl uenza in chicken cells ( 9 ) , but could also be applicable to mammalian studies. Interestingly, when such a mismatch is introduced between bases 9 and 12 from the 5 ¢ -end of the passenger strand, it can also result in increased RNAi potency ( 23 ) . Preservation of the targeting strand is however essential, as single mismatches with the target can ablate silencing ef fi cacy of the duplex ( 24 ) .…”
mentioning
confidence: 99%
“…The configuration of the anomeric center as well as the purine substitution pattern could be confirmed by the observed chemical shifts in the 1 H and 13 C NMR spectra and the 3 other β-hexopyranosyl nucleosides [22][23][24]. The distinction between N 7 or N 9 substitution at the purine scaffold can be achieved by the chemical shift of purine carbon 5.…”
Section: Chemistrymentioning
confidence: 84%
“…Nucleoside synthesis can be performed by a two steps procedure, starting with the acetylation [12] or halogenation [13,14] of suitable precursors, followed by reaction with the heterocyclic base. A direct access to nucleosides can be gained by Lewis acid activation with tin chloride [15,16] or TMSOTf [17] of methyl glycosides in a reaction employing a persilylated purine.…”
Section: Chemistrymentioning
confidence: 99%